Alteration of initial and residual healing potential of asphalt binders due to aging, rejuvenation, and polymer modification. Issue 2 (1st February 2022) - Asadi, Babak; Tabatabaee, Nader
Abstract : Asphalt binders are known to exhibit an inherent ability to repair damage. Such self-healing potentially affects the fatigue damage performance of bituminous materials. There are contradicting findings about the effects of aging and polymer modification on healing. The effectiveness of rejuvenating agents also has not been sufficiently addressed. In the present study, three healing indices have been defined to provide a more complete representation with which to quantify the healing potential of binders. These indices have been defined using damage characteristic curves derived from interrupted linear amplitude sweep tests. Initial healing (IH) describes the immediate reduction in the damage accumulated after the rest period. Residual healing (RH) shows the lasting effect of healing and total healing (TH) is a combination of IH and RH. The results demonstrate that IH does not present a complete picture of healing, particularly at low and intermediate levels of damage. While, RH better exhibits the detrimental effect of aging, the healing ability of SBS (styrene–butadiene–styrene) binder at higher damage levels, and the positive effect of the use of the rejuvenating agent. The healing model shows that, irrespective of the healing index and binder, the effect of loading interruptions at higher levels of damage, along with increased stiffness because of aging, prevail over the positive effects of an increase in the duration of the rest period.